Genetic diversity and population structure of two subspecies of western honey bees (Apis mellifera L.) in the Republic of South Africa as revealed by microsatellite genotyping - Amin Eimanifar; Johanna T. Pieplow; Alireza Asem; James D. Ellis (PeerJ, 2020)
Apis mellifera scutellata and Apis mellifera capensis, two native subspecies of western honey bees in the Republic of South Africa (RSA), are important to beekeepers in their native region because beekeepers use these bees for honey production and pollination purposes. Additionally, both bees are important invasive pests outside of their native ranges. Recently, whole mitogenome sequencing and single nucleotide polymorphisms were used to study their genetic diversity. To add to our knowledge of the molecular ecology of both bees, we tested the ability of microsatellites to be used as a tool to discriminate between A.m. capensis and A.m. scutellata. We analyzed the genetic variability and overall population structure of both bee subspecies and hybrids of the two by genotyping individuals collected from RSA (N = 813 bees from 75 apiaries) at 19 microsatellite DNA loci. Overall, populations averaged between 9.2 and 11.3 alleles per locus, with unbiased heterozygosity values ranging from 0.81 to 0.86 per population. Bayesian clustering analyses revealed two distinct evolutionary units, though the results did not match those of earlier morphometric and molecular analyses. This suggests that the microsatellites we tested were not sufficient for subspecies identification purposes, especially for Cape and hybrid bees. Nevertheless, the microsatellite data highlight the considerable genetic diversity within both populations and a larger-than-expected hybridization zone between the natural distributions of A.m. capensis and A.m. scutellata.